Optimal energy management for electric aircraft. - Omar, Baba S. A. (Cranfield University, 2012)
Current technological advances in aviation are geared towards a more "electric aircraft"; seen as a step towards making the aircraft more efficient, reducing emissions and minimising environmental impact. This thesis investigates the feasibility of using an electric hybrid system consisting of a 1.2KW proton exchange membrane fuel cell (PEMFC), three 12V lead acid batteries, a unidirectional stepdown DC/DC converter, a bidirectional DC/DC converter to power a small aircraft. Using this hybrid configuration the desired power for different flight phases could be achieved. The advantage of PEMFCs is their high power density, low volume and light weight. They operate at relatively low temperatures that allow them to start up quickly without a warming up time. The thesis starts with a literature review of fuel cell technology and a description of a simulation model for the hybrid system developed using MATLAB/Simulink. Initial experimental results for model validation and the system components performance characteristics will be presented. The experimental data were obtained using 1.2kW Nexa power module FC. With regards to the power management aspect, two control strategies have been applied: (1) a traditional (PID) controller was designed and implemented in hardware-in- the-loop to control the battery current via the bidirectional DC/DC converter in the hybrid system, and, (2) replacing the PM controller with a fuzzy logic controller (FLC), because significant time delays were found under PID control. The FLC was implemented to manage the power between two sources in the hybrid system because there are many reports in the literature of successful application of FLC to distribute power between different sources in automotive applications. FLC design was based on the following principle: the PEMFC is the main power supply for the electric engine driving the propeller and it has to be operated at optimal efficiency. In the case that the fuel cell cannot completely meet the power demands in any of the flight phases, the battery will provide a short power burst demand as required. At the same time the FC should keep the battery adequately charged at all times. The controller's input variables are the electric engine power demand and battery state of charge represented by the battery voltage. The output variable is the bidirectional DC/DC converter output power. The use of a FLC allowed the system to operate at an optimal efficiency, satisfying the aircraft's power demand during different flight phases.
Keywords: Proton exchange membrane fuel cell (PEMFC); fuel cell technology; fuzzy logic controller; electric hybrid system; MATLAB/Simulink; power distribution